2014
DOI: 10.1055/s-0034-1368352
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Furofuran Lignans from the Roots of Anemopsis californica

Abstract: Topical preparations of Anemopsis californica have been used by Native American tribes in the southwestern United States and northern Mexico to treat inflammation and infections. We report results of bioassay-guided isolation conducted on a sample of A. californica roots. The furofuran lignans sesamin (1) and asarinin (2) were isolated and shown to have MIC values ranging from 23 to 395 µM against five different species of environmental nontuberculous mycobacteria. These findings are significant given that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Sesamin has not inhibited the growth of Mycobacterium tuberculosis [ 372 ]. Bussey and coworkers [ 373 ] reported low MIC values, ranging from 8 to 150 µg/mL, for sesamin in nontuberculous mycobacteria. Their results suggested that sesamin and asarinin (episesamin) likely accounted for the medical effects of roots of Anemopsis californica , which is used in the folk medicine of North American tribes, and which contains high levels of both lignans.…”
Section: Biological Activities Of Lignansmentioning
confidence: 99%
“…Sesamin has not inhibited the growth of Mycobacterium tuberculosis [ 372 ]. Bussey and coworkers [ 373 ] reported low MIC values, ranging from 8 to 150 µg/mL, for sesamin in nontuberculous mycobacteria. Their results suggested that sesamin and asarinin (episesamin) likely accounted for the medical effects of roots of Anemopsis californica , which is used in the folk medicine of North American tribes, and which contains high levels of both lignans.…”
Section: Biological Activities Of Lignansmentioning
confidence: 99%
“…The CHCl 3 extract was subjected to various column chromatography procedures, and four compounds were isolated. Structures of known compounds ( 1 – 4 ) were elucidated by comparing spectroscopic data to published values ( Bussey et al, 2014 ) and identified as asarinin ( 1 ; 124.9 mg) ( Navarrete et al, 2003 ; Han et al, 2015b ), secoisolitsealiicolide B ( 2 ; 49.9 mg) ( Cheng et al, 2010 ), secolincomolide A ( 3 ; 34.1 mg) ( Tsai et al, 2002 ), and secomahubanolide ( 4 ; 22.4 mg) ( Cheng et al, 2005 ) (Supplementary Figures 2 , 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Anemopsis californica (AC), belonging to the Saururaceae family, predominantly inhabits southwestern North America [ 22 ]. The root powder of AC can be used as a spice and the seeds can be utilized to make bread and various dishes.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary analysis of the phytochemical composition of the ethanolic extracts of AC showed that they included tannins, steroids, coumarins, flavonoids, and phenols [ 24 ]. In addition, the isolation of active compounds from AC extracts have resulted in the identification of sesamin and asarinin [ 22 ]; meanwhile, the most abundant volatile components of AC essential oil were shown to be methyl eugenol (57%), α-pinene (11.7%), elemicin (13.2%), and piperitone (16.2%) [ 23 ], which have been well studied for their antioxidant and anti-aging properties [ 25 , 26 , 27 ]. Studies also confirmed the antioxidative [ 28 ], anti-bacterial [ 22 ], and anti-cancer [ 29 ] effects of AC essential oil and plant extract.…”
Section: Introductionmentioning
confidence: 99%